2000
DOI: 10.1159/000027747
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Neck Dissection in Cancer of the Larynx

Abstract: Cancer of the larynx is a common problem in a head and neck oncological surgical practice; as such, pathology departments supporting such surgical practices will examine cervical lymph node dissection specimens with some frequency. Issues to be settled among pathologists and surgeons include – How precise an anatomic dissection of the specimen is called for? What histological features of the specimen will be of most use to the clinicians who are devising a course of postoperative therapy for the patient? What … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…28 Studies have shown that routine evaluation misses up to 21% of disease nodes. It is suggested that SSS with H&E and IHC, and molecular methods may help to identify smaller metastatic deposits.…”
Section: Discussionmentioning
confidence: 99%
“…28 Studies have shown that routine evaluation misses up to 21% of disease nodes. It is suggested that SSS with H&E and IHC, and molecular methods may help to identify smaller metastatic deposits.…”
Section: Discussionmentioning
confidence: 99%
“…19 This, in reality, is an incomplete examination, where central sections serve as a proxy for the whole node. If deposits were small and present in other regions of the node, they would be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this term has been used to describe nodal disease detected not by clinical investigation, but by conventional histopathological examination of the neck dissection specimens (7). These metastatic deposits are small enough to evade detection by both palpation and radiographic examinations.…”
Section: The Status Of Cervical Lymph Nodesmentioning
confidence: 99%